Promoting Women’s Empowerment Through Grassroots Solidarity: A Case Study of Mothers’ Associations in Benin - Rouhani, Leva (Université d'Ottawa / University of Ottawa, 2021)
In Benin, women in general and rural women in particular are central to the development and sustenance of the household, community, and society at large. Yet, often, they lack the agency, as a result of limited education, life skills, and resources, to contribute to community development, or the structures in place (laws, religious beliefs, policies, and institutions) limit women’s ability to participate in community development. As a result of their limited agency and the unequal structures in society, women in Benin have often been denied participation in decisions around education, health, economy, and agriculture. While women are key actors in all these sectors, they are often not represented sufficiently in the discussions that shape their lives. Women in Benin have collectively organized into associations to address these issues. Associations such as Mothers Associations (MAs) in Benin, have emerged with the specific purpose of improving the education of their daughters. MAs function under the umbrella of Parent Associations (PAs) to address issues of particular concern to girl students. While PAs have helped to improve basic education by putting pressure on school administrators and political leaders to address the quality of schools, these associations have been primarily male dominated, rarely identifying the specific barriers to education for girls. My dissertation has three main objectives: to assess how MAs in Benin have collectively mobilized to enhance the quality of education for schoolgirls; to determine whether MA activities and mobilization efforts have led to women’s empowerment and influence within their respective communities; and to examine whether MAs have had an impact on changing harmful social norms. Overall, the objective of this research is to examine how members of the MAs have used their collective agency to enhance gender equality within the school and community life. Through a critical feminist approach and applying a socio-ecological model, I examine the process in which African women have mobilized, collaborated, and advocated for girls’ education in ways that subtly undermine the harmful relations of power that govern their position in society.
Keywords: Gender equality; Girls' education; Collective organization; Women's empowerment; Africa; Benin